2016
DOI: 10.1016/j.jphotochem.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limits of structurally-diverse light-harvesting Ru(II) metal-organic chromophores for photodynamic therapy

Abstract: The synthesis of Ru(II) derivatives [(AnthbpyMe)(bpy)Ru(dpp)] 2+ (2) and [(AnthbpyMe) 2 Ru(dpp)] 2+ (3), and the analysis of their excited state properties as well as their photocytotoxicity against glioma cells are reported. Complexes 2 and 3 absorb visible light with metal-to-ligand charge transfer (MLCT) transitions at λ max = 459 nm (16,000 M-1 cm-1) and λ max = 461 nm (21,000 M-1 cm-1), respectively. The complexes exhibit bichromatic properties with the 3 MLCT emission centered at λ em = 661 nm and λ em =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…8 We have shown that complexes 2 and 3 efficiently absorb light throughout the visible region, facilitated by several MLCT transitions with λ max = 459 nm (ε = 16,000 M −1 cm −1 ) and 461 nm (ε = 21,000 M −1 cm −1 ), respectively. 7 Upon excitation the anthracene-[Ru]-dpp hybrid arrangement provides multiple pathways, singlet-singlet, triplet-triplet, and/or singlet-triplet, for deactivation from the 3 MLCT excited state through energy/electron transfer, which is speculated to enhance the PDT potency that was observed for these complexes against mammalian cells in preliminary experiments, 7 as also recently suggested for anthracene-[Ru]-bpy complexes. 6 …”
mentioning
confidence: 70%
See 3 more Smart Citations
“…8 We have shown that complexes 2 and 3 efficiently absorb light throughout the visible region, facilitated by several MLCT transitions with λ max = 459 nm (ε = 16,000 M −1 cm −1 ) and 461 nm (ε = 21,000 M −1 cm −1 ), respectively. 7 Upon excitation the anthracene-[Ru]-dpp hybrid arrangement provides multiple pathways, singlet-singlet, triplet-triplet, and/or singlet-triplet, for deactivation from the 3 MLCT excited state through energy/electron transfer, which is speculated to enhance the PDT potency that was observed for these complexes against mammalian cells in preliminary experiments, 7 as also recently suggested for anthracene-[Ru]-bpy complexes. 6 …”
mentioning
confidence: 70%
“…7 The PAH, anthracene, has shown substantial promise for enhancing the PDT reactivity of Ru(II) complexes. 78 Anthracene can by itself intercalate into the DNA double helix and, upon irradiation with UV light, oxidize adjacent sites in the DNA molecule though reactive oxygen species (ROS) or anthracene-derived cation radicals.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Complexes of the type [Ru(bpy) 2 (R-dppz)] 2+ (where R is either NH 2 , Ru6 or OMe, Ru7 , Figure 10) intercalated with DNA via the R-dppz ligand and achieved phototoxic indices of >150 and 42, respectively, against HeLa cells when irradiated with light at 420 nm (Table 4) [62]. A polypyridyl ruthenium complex incorporating an appended anthracene demonstrated photocleavage of DNA through both ruthenium-derived singlet oxygen and anthracene-derived radicals, as well as light-induced cytotoxicity in F98 glioma cells [65,66]. Ruthenium arene “piano-stool” complexes are very prominent anticancer agents, and some studies have reported a dual-binding mode in which ruthenation occurs through a leaving group while the p -cymene group intercalates between nearby bases [67].…”
Section: Rutheniummentioning
confidence: 99%